A GABAergic and peptidergic sleep neuron as a locomotion stop neuron with compartmentalized Ca2+ dynamics - Wagner Steuer Costa; Petrus Van der Auwera; Caspar Glock; Jana F. Liewald; Maximilian Bach; Christina Schüler; Sebastian Wabnig; Alexandra Oranth; Florentin Masurat; Henrik Bringmann; Liliane Schoofs; Ernst H. K. Stelzer; et al. (Nature Communications, 2019)
The GABAergic and peptidergic neuron RIS mediates sleep in Caenorhabditis elegans. The authors demonstrated here that RIS also functions as a locomotion stop neuron. Its optogenetic stimulation caused acute and persistent inhibition of locomotion, and brief intrinsic RIS activity preceded slowing.